Revenue sources of local governments persistent challenges and emerging opportunities - Benton, J. Edwin 1950- (2024)
"With limited fiscal capabilities, effective and efficient budgeting is a necessity for each of the five types of local governments in the United States. Acknowledging the critical (but often overlooked) part that raising enough revenue to fund desirable and programs plays in the budgetary process, this book offers an exclusive and comprehensive examination of the revenue side of the budget. It provides much-needed and wide-ranging context for examining and understanding local government revenues and local government revenue policy. Author J. Edwin Benton presents a comprehensive overview of the revenue structure for local governments, in general, and for counties, municipalities, townships, special districts, and school districts, in particular. The bulk of the book meticulously examines the historical patterns and trends in revenue usage by local governments, and provides explanations for variations among different units of government, states, and regions of the country. The book enhances our understanding of the most relevant research and aids in refining theories that seek to explain why local governments (or different types of local governments) rely more on certain kinds of revenues. It also offers immediately applicable real-world case studies on revenue-raising capabilities, practicalities, and experiences of local governments around the country. It will be of enormous interest to public budgeting practitioners, students, and scholars"-- Provided by publisher.